Peramalan Jumlah Konsumsi Energi Listrik di PT PLN (Persero) Rayon Bukittinggi Menggunakan Metode Arima - Ginna Melinda; Minora Longgom Nasution; Helma Helma (Journal of Mathematics UNP, 2019)
Abstrak –As a provider of electricity revenues of PLN Rayon Bukittinggi can decline. This is due to an imbalance between electric energy produced by the requested consumer. To increase the income of PLN Rayon Bukittinggi by predicting the amount of electrical energy needs far before the electrical energy used by consumers. One method of divination used i.e methods ARIMA. Formulation of the problem in this research is "how forecasting the amount of electrical energy consumption for PT PLN (Persero) Rayon Bukittinggi from June 2016until May 2017 using ARIMA". The results obtained in this study was getting models ARIMA (1,1,1)(0,1,1)12 as a suitable model, with a form ofmodelYt =Yt-1 -0,4629Yt-1 +0,4629Yt-2 +Yt-12 -Yt-13 +0,4629Yt-13 -0,4629Yt-14 + et - 0,9263et-1 - 0,7499 et-12 +0,6946 et-13.Keywords– Bukittinggi,Electric, Forecasting, ARIMA